Dietary supplement intake in Greek team sports athletes - Noutsos, K. S. (Journal of Athletic Enhancement, 2015)
The scope of this study was to research the use of dietary supplements by athletes in team sports. More specifically, it was to compare the frequency, type and reasons for consumption, as well as the nutritional influences, sources of information and the purchase outlets between men and women among levels of performance and among training volumes. A total of 1,811 athletes from team sports (handball, basketball, volleyball, soccer and water polo) participated in the study. All participants responded to a questionnaire and were asked to record each supplement they currently were taking or had been taking over the last six months. The results showed that 36.7% of the sample used dietary supplements. Dietary supplements were significantly lower for those in volleyball than those in other sports (F=5.2, p<0.001). Female athletes consumed significantly fewer dietary supplements than their male counterparts (?2=12.00, p<0.001). The higher the level of achievement (?2=196.6, P<0.001) or training volume (?2=48.25, p<0.001), the higher the percentage of athletes who consumed supplements. They preferred to consume mainly proteins (43.8%) with an aim to primarily increase endurance (34.8%). The coach (34.0%) was the major dietary counselor for the majority of athletes, while pharmaceutical outlets were the main providers. It is worth noting that 16.1% of athletes were unaware of the names of the products they were using.